Sosialisasi dan Edukasi Pernikahan Dini di SMPN 1 Semboro Jember - Deviana Putri Ari Sandy (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Early marriage remains a persistent social issue in Indonesia, particularly in rural areas. Data from the Central Statistics Agency (BPS) in 2023 indicate that the prevalence of child marriage reached 9.02%, meaning approximately 1 in 11 girls were married before the age of 18. This condition has multidimensional consequences, including increased risks to maternal and child health, psychological distress, decreased school participation, and violations of children’s rights. To address this problem, an educational activity on the prevention of early marriage was carried out at SMP Negeri 1 Semboro. The method applied was a participatory approach involving outreach, interactive material delivery, group discussions, reflection, and motivational sessions. The material covered the definition and legal framework of early marriage, its impacts on physical, mental, social, educational, and legal aspects, as well as strategies to prevent it through delaying marriage and prioritizing education. The results showed that eighth and ninth grade students participated enthusiastically, demonstrated improved understanding of the risks of early marriage, and were able to design medium-term life plans before marriage. Constraints such as limited time and students’ reluctance to express opinions were successfully overcome through interactive methods. This activity contributed to raising adolescents’ awareness and strengthening early marriage prevention efforts